2012
DOI: 10.1155/2012/278045
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Curve of Gastric Intestinal Metaplasia Interpretation on the Images Obtained by Probe-Based Confocal Laser Endomicroscopy

Abstract: Background. Reading the results of gastric intestinal metaplasia (GIM) with probe-based confocal laser endomicroscopy (pCLE) by the expert was excellent. There is a lack of study on the learning curve for GIM interpretation. Therefore, we conducted a study to explore the learning curve in the beginners. Material and Method. Five GI fellows who had no experience in GIM interpretation had been trained with a set of 10 pCLE video clips of GIM and non-GIM until they were able to interpret correctly. Then they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
0
16
0
1
Order By: Relevance
“…Fluorescein Alcon, which is clinically approved for intravenous application and is regularly applied for pCLE in the gastrointestinal tract [19,20], is suitable to stain spermatozoa after topical application after incision of the tunica albuginea. After staining the spermatozoa generally stay motile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescein Alcon, which is clinically approved for intravenous application and is regularly applied for pCLE in the gastrointestinal tract [19,20], is suitable to stain spermatozoa after topical application after incision of the tunica albuginea. After staining the spermatozoa generally stay motile.…”
Section: Discussionmentioning
confidence: 99%
“…As in all new imaging techniques, there is an associated learning curve for the interpreter [19] to identify all cells of spermatogenesis as displayed by pCLE. In the near future the interpretation might be facilitated by staining spermatozoa with a spermspecific FITC labelled antibody.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The agreement between interpretation by experienced endoscopists and histology for gastric intestinal metaplasia was also higher than that for inexperienced endoscopists (K=0.864 vs 0.217). Pittayanon et al 47 demonstrated that trainees with no experience in intestinal metaplasia interpretation could achieve high reading accuracy and substantial interobserver agreement after training with 10 sets of CLE video clips. Trainees on achieving high reading accuracy were shown to maintain their high quality of reading skill.…”
Section: Confocal Laser Endomicroscopy (Cle)mentioning
confidence: 99%
“…Guo et al19 additionally demonstrated 98% sensitivity and 95% specificity for GIM using confocal microscopy. Notably, the learning curve for pCLE detection of GIM is short, typically obtaining acceptable intraobserver agreement with 1 to 2 hours of training 21. Yet to be explored is whether pCLE can improve the diagnosis of dysplasia following gastric endoscopic mucosal resection or endoscopic submucosal resection.…”
Section: Confocal Microscopy For Assessment Of Gastric Intestinal Metmentioning
confidence: 99%